Evaluation of different root canal filling techniques in severely curved canals by micro-computed tomography - Betul Aycan Alim; Yıldız Garip Berker (Elsevier, 2020)
Aim: To fill the severely curved root canals with different filling techniques and to compare these techniques using micro-computed tomography (micro-CT). Materials and methods: Sixty extracted mandibular first molars (degree of root canal curvature >25°) were selected. All samples were divided into four groups and filled with one of the following techniques: lateral condensation, single-cone, continuous-wave obturation, and core carrier. After they were scanned by micro-CT, the total area, filled area and void area of the root canal were calculated. The Mann-Whitney U and Kruskal-Wallis tests were used for statistical analysis (p < 0.05). Results: It was shown that significantly more filling material was used in the lateral condensation and core carrier technique groups at 2 and 5 mm than in the single-cone and continuous-wave obturation technique groups (p < 0.05). It was observed no statistically significant difference at 8 mm (p > 0.05). Conclusion: No technique could completely fill in root canal. Regarding the coronal part, all techniques can be used for more effective filling as long as a good condensation is achieved. The use of a plugger with an optimal size according to the localisation of root canal curvature and the choice of a heat-resistant root canal sealer affects the success of the treatment in the thermoplastic techniques.